IS HEALTHY NEUROTICISM ASSOCIATED WITH HEALTH BEHAVIORS AND OUTCOMES? A CORDINATED ANALYSIS. (11th November 2018) - James, B; Graham, E K; Turiano, N A; Weston, S J; Čukić, I; Wisniewski, K; Makkar, S; Harrison, F
Abstract: Higher Neuroticism is typically linked to poorer health behaviors and a heightened risk of adverse health outcomes. However, several studies showed that, when combined with higher Conscientiousness, higher Neuroticism may in fact be linked to a lowered risk of poorer health, thus rendering the interaction between Neuroticism and Conscientiousness as "Healthy Neuroticism". Here, we aim to establish the replicability of Healthy Neuroticism using health behaviors (alcohol consumption, smoking, physical activity) and chronic condition incidence (diabetes, hypertension, heart disease) as outcomes. We do so by conducting a coordinated analysis of 14 prospective cohorts, from 5 countries, with a combined N of nearly 50, 000. Ours is the first large-scale systematic effort to estimate replicability and generalizability of Healthy Neuroticism. We discuss implications for future research in the field of lifespan personality and health.